The Story of Loved Ones as Description Learning Media in the Elementary School - Abdul Rahman Rahim (STAI Hubbulwathan Duri, 2022)
Writing lessons are generally a scourge for learners because the management of learning is less attractive, effective, and efficient. The purpose of this research is to improve the ability to write the description text of students’grade V at SD Pertiwi Makassar by using the story of loved ones’media. The research method used wasa one-group pretest-posttest design, namely a research design that was given a pre-test before being given treatment and a post-test after being given action or treatment. The thing done in the implementation of the experiment was to assign to a sample that had not been given treatment or called a pre-test to measure the initial ability to write the descriptivetext. The conclusion of this research was the result of writing a descriptivetext of students’grade V at SD Pertiwi Makassar using the story of loved ones’ media increased by looking at the improvement of the average score of acquisition from 35.62 on the pre-test to 67.04. This scorewas less than 0.98 to achieve minimum completeness, which was 68.